Asymmetric information, sorting, and the gender price gap - Dickinson, Jeffrey; Koo, Jawoo (International Food Policy Research Institute, 2022)
This paper analyzes transaction data from agricultural surveys carried out in five countries in low-and-middle-income countries to test for a difference in the prices received by men and by women marketing the same crop in the same village. In a unique finding, we identify a gap between the price received by women and the price received by men on three separate continents. Echoing similar results from other countries in sub-Saharan Africa, using mobile phone ownership and use data, we provide evidence to suggest that women farmers likely suffer from unequal access to information. The presence of asymmetric information is therefore indicated to be a limiting factor in women’s ability to receive a fair unit price.